Assessment of the stiffness of 3D cut welded connections with CHS columns and through I-BEAMS. (October 2020) - Di Benedetto, S.; Latour, M.; Rizzano, G.
Highlights: Experimental tests on the analysed connection typology are presented and discussed. A FE model of the connection is validated against the experimental results. A parametric analysis has been performed exploiting the validated FE model. The component method approach has been applied to define a design formula. The accuracy of the equation is verified against FE data showing high accuracy. Abstract: A novel solution offered by the 3D Laser Cutting Technology, in the field of civil engineering, consists in the possibility of coupling hollow section columns with through I-beams. Such a kind of joint is alternative to the configuration with the I-beam simply welded to the external surface of the hollow profile for which Eurocode 3 part 1.8 provides specific rules for the strength calculation. The mechanical behaviour of joints with through I-beams is improved due to the higher flexural strength and stiffness of the connection. Nevertheless, no guidelines are currently available in national or international codes which allow to safely adopt this structural detail in practice. For such a reason, aiming at filling the knowledge gap about the structural behaviour of CHS to through I-beam joints, a research activity including experimental, numerical and analytical work, has been recently carried out at the STRENGTH laboratory of the University of Salerno. Specifically, the experimental phase has involved the execution of a cyclic and a monotonic test on a sub-assembly representative of the studied connection. The obtained results have been exploited to validate a numerical model developed in an FE software. This has allowed to simulate the behaviour, under monotonic loading, of other 29 connections, whose values of stiffness have been used to calibrate the coefficients of a design equation for the stiffness prediction based on the component method. The proposed equation has proved to be reliable in the stiffness prediction of such a kind of joints. Its accuracy in predicting the stiffness of joints with through-all beams is equal on average to 1, with a coefficient of variation equal to the 9%.